Identification of blood transcriptome modules associated with suicidal ideation in patients with major depressive disorder - Min Wang; Hailin Xiang; Jinxue Wei; Yikai Dou; Yushun Yan; Yue Du; Huanhuan Fan; Liansheng Zhao; Rongjun Ni; Xiao Yang; Xiaohong Ma (Scientific Reports)
Abstract The risk of suicide in patients with major depressive disorder (MDD) poses a major concern, with studies suggesting that genetics may be a contributing factor. Although there are many transcriptomic studies on postmortem brain tissue related to suicidal behavior, the blood transcriptional mechanisms of suicidal ideation (SI) remain unknown. This study utilized a weighted gene coexpression network analysis (WGCNA) approach to investigate the associations between gene coexpression modules and SI in individuals with MDD using peripheral blood RNA-seq data from 75 MDD patients with SI (MDD_SI), 82 MDD patients without SI (MDD_nSI), and 149 healthy controls (HC). An ANCOVA was conducted to assess differences in gene coexpression modules among groups, with age and sex included as covariates. The gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) databases were used to annotate module functions. Results indicated that the magenta module (associated with RNA splicing processes) differentiated MDD_SI from MDD_nSI (p = 0.021), while the green module (related to immune and inflammatory responses) distinguished MDD_SI from HC (p = 0.004). Additionally, three modules showed differences between MDD_nSI and HC: magenta (p = 0.009), brown (related to innate immunity and mitochondrial metabolism; p = 0.001), and turquoise (associated with energy metabolism and neurodegeneration; p = 0.005). Our findings highlight that gene expression regulation, immune response, and inflammation may be linked to SI in patients with MDD, while pathways associated with innate immunity, energy metabolism, mitochondrial function, and neurodegeneration appear to be more broadly related to MDD.